Mathematical Concepts and Empirical Study of Neighborhood Irregular Topological Indices of Nanostructures TUC4C8p,q and GTUC p,q - Shahid Zaman; Asad Ullah; Rabia Naseer; Kavi Bahri Rasool (Journal of Mathematics, 2024)
A topological index is a structural descriptor of any molecule/nanostructure that characterizes its topology. In the QSAR and QSPR research, topological indices are employed to predict the physical characteristics associated with bioactivities and chemical reactivity within specific networks. 2D nanostructured materials have many exhibit numerous chemical, mechanical, and physical features. These nanomaterials are exceptionally thin, displaying high chemical functionality and anisotropy. For applications necessitating robust surface interactions on a small scale, 2D materials stand out as the optimal choice due to their expansive surface area and status as the thinnest among all discovered materials. This paper characterized the neighborhood irregular topological invariants of nanostructures TUC4C8[p, q] and GTUC[p, q] and derived closed form expressions for them. A comparative analysis is then performed on the basis of these computed indices.